Proceso atención de enfermería en paciente adulto con tumor benigno lipomatoso de piel y tejido subcutáneo. - Gavica Pacheco, Emilio Andrés (2022)
The purpose of this paper is to develop the nursing care process in a 57-year-old male patient diagnosed with diabetes mellitus 5 years ago who comes to the emergency area due to a clinical picture of ± 3 days of evolution accompanied by hyperthermia, general malaise, intense pain in the lower left extremity located in the calcaneus due to a semi-deep injury caused by a rusty sharp object. Erythema around the wound plus purulent and foul-smelling discharge is also seen. Vital signs were taken; blood pressure 100/60 mmHg, heart rate 105 X1, breathing 23 X1, temperature 38º C, oxygen saturation 94%. Blood count, blood chemistry and foot X-ray tests are performed. At first instance, a heterogeneous mass with a fatty component is evidenced, giving the diagnosis of a calcaneal spur plus a benign lipomatous tumor and septicemia. Patient is transferred to the internal medicine area for an urgent surgical procedure. We proceeded to develop and apply the Nursing Care Process to the patient, using the Nanda, Nic and Noc taxonomies, to meet the objectives proposed in this clinical case study.